2015
DOI: 10.18553/jmcp.2015.21.7.596
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation/Interruption of Warfarin Therapy in Patients with Nonvalvular Atrial Fibrillation

Abstract: BACKGROUND: Use of warfarin is standard of care for stroke prevention in patients with atrial fibrillation (AF). However, AF patients experience high rates of warfarin discontinuation/interruption, resulting in increased health risks and health care costs. As such, it is important to study the rates and predictors of warfarin discontinuation/interruption in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 40 publications
3
25
2
1
Order By: Relevance
“…This prospective study of patients on dabigatran showed the probability of persistence over 2 years exceeded 70%, which is higher than previously reported persistence rates to warfarin 3,4 and claims-based estimates of persistence to NOACs. 8,10 Furthermore, it was also shown that the greatest risk for discontinuation is in the early period following treatment initiation.…”
Section: Discussioncontrasting
confidence: 82%
“…This prospective study of patients on dabigatran showed the probability of persistence over 2 years exceeded 70%, which is higher than previously reported persistence rates to warfarin 3,4 and claims-based estimates of persistence to NOACs. 8,10 Furthermore, it was also shown that the greatest risk for discontinuation is in the early period following treatment initiation.…”
Section: Discussioncontrasting
confidence: 82%
“…29 The discontinuation of OA for patients with NVAF has not improved with the new direct-acting OA, 30 and has been associated with younger age, anemia, bleeding, frailty, low life expectancy, hospitalizations and emergency department visits. 22 In the present study, OA was discontinued for one of every four patients. The discontinuation was associated with the risk of hemorrhage, and the absence of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 92%
“…In a survey of cardiologists, geriatricians and primary care physicians, both conditions were frequently mentioned for not starting OA therapy . In another study with the American MarketScan Database, both anemia and bleeding were associated with treatment discontinuation . Patients have a different perception of risks than physicians .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During 12 months after warfarin initiation, 12% had interruption without discontinuation, and 43% had discontinuation among a total of 58,593 patients with non-valvular atrial fibrillation [1] . The risk of an ischemic stroke is almost 60% greater during warfarin discontinuation for any reason in patients with atrial fibrillation [2] .…”
Section: Introductionmentioning
confidence: 99%